Morphological and Anatomical Changes by Cochicine in Seedling of Impatiens balsamina L. - Wiendra, Ni Made Sastriyani; Pharmawati, Made (Advances in Tropical Biodiversity and Environmental Sciences; Vol 3 No 2 (2019): ATBES, 2019)
Impatiens balsamina L. is a plant that is widely cultivated in Bali. The flower of this plant is used as a component of offering in Hindu religious ceremonies. The flower petals are thin and wilt easily, therefore genetic modification is needed to get better quality. This research aimed to study the effect of 0.01% colchicine with soaking periods of 4 hours, 8 hours, 12 hours and 24 hours to seedlings of I. balsamina. Seeds of I. balsamina were germinated and sprouted seeds were treated with 0.01% colchicine for 4 hours, 8 hours, 12 hours and 24 hours. The sprouted seeds were then transfer to polybag with soil media. The experiment was designed with randomized blok design with five replicates. Observations were done on plant height, length and width of leaf, stem diameter, number of stomata as well as observation on plant stem cortex cells. Results showed that colchicine reduced plant height at three weeks after planting, while plant stem diameter increased. Control plants had the smallest leaf length and width. The number of stomata decreased at plants derived from colchicine treated sprouted seeds and the lowest stomatal number observed was at soaking duration of 24 hours.